2020
DOI: 10.1108/oir-01-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of polarity of post-publication peer review to citation count

Abstract: PurposeThe purpose of this study is to investigate the relationship of the post-publication peer review (PPPR) polarity of a paper to that paper's citation count.Design/methodology/approachPapers with PPPRs from Publons.com as the experimental groups were manually matched 1:2 with the related papers without PPPR as the control group, by the same journal, the same issue (volume), the same access status (gold open access or not) and the same document type. None of the papers in the experimental group or control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Finally, and also importantly, given that science, and its replication, may be in a state of crisis, including the core principle of industry-wide trust, it would be important to evaluate the post-publication peer reviewer (PPPR) reports that existed at Publons [ 93 ], and to appreciate their content in WoS to assess whether positive PPPR reports (praising research) outweigh negative ones (criticizing research or calling out errors or possible fraud). Goldstein [ 94 ] noted a deficit of PPPR reports relative to pre-publication reports at Publons, while also noting bias towards, or in favor of, life sciences (health and medical sciences), while Publons metrics were weakly and insignificantly correlated with bibliometric and altmetric indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, and also importantly, given that science, and its replication, may be in a state of crisis, including the core principle of industry-wide trust, it would be important to evaluate the post-publication peer reviewer (PPPR) reports that existed at Publons [ 93 ], and to appreciate their content in WoS to assess whether positive PPPR reports (praising research) outweigh negative ones (criticizing research or calling out errors or possible fraud). Goldstein [ 94 ] noted a deficit of PPPR reports relative to pre-publication reports at Publons, while also noting bias towards, or in favor of, life sciences (health and medical sciences), while Publons metrics were weakly and insignificantly correlated with bibliometric and altmetric indicators.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because some post-publication peer reviews on Publons.com were not real post-publication peer reviews. A previous study revealed that some post-publication peer reviews on Publons.com were structured like pre-publication peer reviews (Zong et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This might be because some post-publication peer reviews on Publons.com were not real post-publication peer reviews. A previous study revealed that some post-publication peer reviews on Publons.com were structured like prepublication peer reviews (Zong et al, 2020). That is, reviewers might transfer their prepublication peer reviews of the articles they reviewed to the post-publication peer review of the articles on Publons.com.…”
Section: Identifying Excellent Peer Reviewersmentioning
confidence: 99%
“…The jointed width and depth component model was proposed, and the PRC was represented with a matching mechanism to predict the citations. Zong et al. (2020a, b) explored whether the sentiment polarity of post-publication PRC from PubPeer, F1000 and ResearchGate affected the citations through content analysis method, control variable method, negative binomial regression analysis and other methods.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, open peer review has attracted more and more scholars' attention. Some scholars found that the citations of papers in open access journals are higher than that in non-open access journals (Vanclay, 2013), and open peer review can improve the citations (Zong et al. , 2020a, b).…”
Section: Related Workmentioning
confidence: 99%